Data Mining Techniques for Web Mining: A Survey - Gheisari, Mehdi; Hamidpour, Hooman; Liu, Yang; Saedi, Peyman; Raza, Arif; Jalili, Ahmad; Rokhsati, Hamidreza (Artificial Intelligence and Applications, 2023)
The data mining (DM) is the computational process that consists of searching, extracting, and analyzing patterns in large data sets, including methods at the intersection of artificial intelligence, machine learning, statistics, and database schemes. Specifically, its primary goal is to extract information from a raw data set and transform it into an expected structure for further use. Moreover, an evolving perspective of DM is web mining (WM), which refers to the whole of DM and related routines. It is used to discover and extract information from web records and services automatically, that is, WM’s purpose is to obtain valuable data from the World Wide Web. Due to its importance, a survey about DM techniques in WM is necessary, as performed in this paper. Received: 30 June 2022 | Revised: 30 September 2022 | Accepted: 25 October 2022 Conflicts of Interest The authors declare that they have no conflicts of interest to this work.